2006
DOI: 10.1016/j.ijgo.2006.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in gestational diabetes

Abstract: Aggressive management for tight glycemic control improves maternal and neonatal outcomes in women with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 20 publications
(21 reference statements)
1
32
0
6
Order By: Relevance
“…Diabetes can cause endothelial dysfunction (Calles-Escandon and Cipolla 2001; Dandona et al 2006), which may contribute to the pathophysiology of PE (Lyell et al 2003; Roberts and Lain 2002; Salas 1999), as supported by studies showing that tight glycemic control reduces the risk of PE in women who had diabetes before becoming pregnant (Crowther et al 2005; Fan et al 2006; Yogev et al 2004). Another study also showed that increasing glucose intolerance among nondiabetics is also associated with PE (Sermer et al 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Diabetes can cause endothelial dysfunction (Calles-Escandon and Cipolla 2001; Dandona et al 2006), which may contribute to the pathophysiology of PE (Lyell et al 2003; Roberts and Lain 2002; Salas 1999), as supported by studies showing that tight glycemic control reduces the risk of PE in women who had diabetes before becoming pregnant (Crowther et al 2005; Fan et al 2006; Yogev et al 2004). Another study also showed that increasing glucose intolerance among nondiabetics is also associated with PE (Sermer et al 1995).…”
Section: Discussionmentioning
confidence: 95%
“…It would seem that the prevention of macrosomia should be the primary goal of GD management. Several studies suggest an increased rate of preeclampsia among women with GD, and a combination of maternal diabetes and pre-eclampsia is associated with poor perinatal outcome (Fan et al, 2006). Untreated or poorly controlled gestational diabetes can hurt the baby.…”
Section: Risk Factors For Gdmentioning
confidence: 99%
“…In recent years there has been a reported increased trend in the prevalence of GD throughout the world, with huge health-care and economic costs (Bellamy et al, 2009). This is particularly the case in developed countries, such as the USA, the UK, Australia, China and New Zealand (Sinha et al, 2003;Ferrara et al, 2004;Joshy & Simmons, 2006;Metzger & Counstan, 1998;Fan et al, 2006;Carolan et al, 2010). The increased prevalence has been recently disputed, suggesting that more cases were identified through more aggressive universal screening.…”
Section: Prevalence Of Gdmentioning
confidence: 99%
“…Respecto a la morbilidad metabólica (hipocalcemia e hipomagnesemia e hiperbilirrubinemia), esta se presentó en un bajo porcentaje en este estudio, comparándose con lo reportado en la literatura mundial, ya que se muestra hasta en un 40% y 30% respectivamente (18). La información en relación a la baja frecuencia de ambas patologías metabólicas neonatales, habría que tomarla con reserva debido a que en el hospital donde se realizó el estudio no es común la búsqueda de hipomagnesemia y, por otro lado, los datos clínicos son semejantes a los de hipocalcemia.…”
Section: Tabla II Morbilidad Neonatal Asociada a La Diabetes Gestacionalunclassified